Pengaruh Kompetensi Sumber Daya Manusia, Komitmen Pimpinan dan Perangkat Pendukung (Teknologi Informasi) Terhadap Penerapan SIPKD (Studi Kasus Pada Pemerintah Kabupaten Kapuas Hulu) - Setiawan, Aris (Jurnal Akuntansi dan Governance Andalas, 2020)
The purpose of this study was to determine and obtain empirical evidence of the influence of human resource competencies, leadership commitment and supporting devices (information technology) on the application of SIPKD to the Kapuas Hulu Regency government. The population in this study were all SKPDs in Kapuas Hulu Regency. Sampling in this study used a survey method with a total of 71 research samples. Hypothesis testing analysis techniques using multiple linear regression analysis. The results of this study indicate that the competence of human resources, the commitment of leaders and supporting devices (information technology) has a positive and significant effect on the implementation of SIPKD in the Kapuas Hulu district government means that the better the competency of human resources they have, the high commitment of leaders and supporting devices (information technology ) the better the application of SIPKD will be better.